The black hole [videorecording (DVD)] - Nelson, Gary, 1934-; Schell, Maximilian; Perkins, Anthony, 1932-1992; Borgnine, Ernest, 1917-2012; Forster, Robert, 1942-2019-; Bottoms, Joseph (Walt Disney Home Video ; Distributed by Buena Vista Home Entertainment, Inc., 2004)
Scientists are all aboard an Earth discovery vessel on a fruitless search for life in space when they encounter a lost spaceship perched on the event horizon of the universe's most powerful phenomenon, a black hole.